Structural Characterization of a-D-Glucan Obtained from Angelica sinensis Roots - Cheng-Gang, Huang; Guan, Ye; Xin-Liang, Wang; Chen, Li; Zhi-Xiao, Li; Yao-Zu, Chen (Asian Journal of Chemistry, 2016)
a-D-Glucan (ASP-1) was isolated from the hot water extract of Angelica sinensis roots by ethanol precipitation, anion-exchange and gel-permeation chromatography. Smith degradation, NMR spectroscopy, composition and methylation analysis confirmed the ASP-1 structure comprises a (1®6) linked a-D-glucopyranosyl backbone, coupled with two branches per unit bonded through a(1®3) linkages, where each branch contains Glc-(1®3)-Glc-(1- and Glc-(1®4)-Glc-(1- chains at either end.